Progesterone levels on the human chorionic gonadotropin trigger day affect the pregnancy rates for embryos transferred at different stages of development in both general and selected IVF/ICSI populations - P. Merviel; S. Bouée; A. S. Jacamon; J. J. Chabaud; M. T. Le Martelot; S. Roche; C. Rince; H. Drapier; A. Perrin; D. Beauvillard (BMC, 2021)
Abstract Background Two meta-analyses have shown that pregnancy and birth rates are significantly higher after blastocyst transfer than after cleaved embryo transfer. Other studies have revealed that a serum progesterone level > 1.5 ng/ml on the trigger day is responsible for premature luteinization and is associated with a low pregnancy rate. The objectives of this retrospective study were to determine whether blastocyst transfer gave higher pregnancy rates than cleaved embryo transfer at day 3 in both the general and selected IVF/ICSI populations, and whether the serum progesterone level influenced the pregnancy rate. Method We studied IVF/ICSI cycles with GnRH antagonist - FSH/hMG protocols in a general population (n = 1210) and a selected "top cycle" population (n = 677), after blastocyst transfer on day 5 or cleaved embryo transfer on day 3. The selected couples had to meet the following criteria: female age < 35, first or second cycle, and one or two embryos transferred. We recorded predictive factors for pregnancy and calculated the progesterone to oocyte index (POI), the progesterone:estradiol ratio (P:E2 ratio), and the progesterone to follicle (> 14 mm) index (PFI). Results In the general population, the clinical pregnancy rate was significantly higher after blastocyst transfer (33.3%) than after cleaved embryo transfer (25.3%; p <  0.01); the same was true for the birth rate (32.1 and 22.8%, respectively, p <  0.01). The differences between blastocyst and embryo transfer groups were not significant in the selected population (respectively 35.7% vs. 35.8% for the clinical pregnancy rate, and 33.9 and 34.9% for the birth rate). The serum progesterone levels on the eve of the trigger day and on the day itself were significantly lower in the pregnant women (p <  0.01). We found a serum progesterone threshold of 0.9 ng/ml, as also reported by other researchers. The POI and the PFI appear to have predictive value for cleaved embryos transfers. Conclusions Blastocyst transfers were associated with higher clinical pregnancy and birth rates than cleaved embryo transfers in a general population but not in a selected population. The serum progesterone levels on the eve of the trigger day and on the day itself predicted the likelihood of pregnancy.